Development and testing of a solar air-heater with conical concentrator - Togrul, IT; Pehlivan, D; Akosman, C (Pergamon-Elsevier Science Ltd, 2004)
The free convection performance of a solar air heater with a cylindrical absorber centred to a conical concentrator for focusing incident solar radiation was studied. The primary objective was to heat air to higher temperatures than those obtainable in flat-plate collectors. The experiments were carried out and the data recorded in summer daytime, considering collector tilting angle and type of absorbing surface as the investigation parameters. It was found that a tilting angle under local latitude would be appropriate for collector installation. Although the efficiency of the heater at free convection conditions was very much smaller than flat-plate solar air-heaters, exit air temperatures reached up to 150 degreesC, which could allow utilisation in high temperature applications. A selective absorber surface improved appreciably the performance of the solar air-heater. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: solar air-heater; conical concentrator; solar tracking